Epigenetic insights into prostate cancer: exploring histone modifications and their therapeutic implications - Sharma, Bunty; Shekhar, Himanshu; Sahu, Anidrisha; Kaur, Damandeep; Haque, Shafiul; Tuli, Hardeep Singh; Sharma, Himanshu; Sharma, Ujjawal (Frontiers in Oncology, 2025)
Prostate cancer is one of the most prevalent malignancies globally. This cancerous condition originates within the prostate gland, an integral part of the male reproductive system. The molecular mechanism underlying cancer is among the key areas of research in the scientific community. Cancer, being a multifactorial disease, is controlled by many factors ranging from environmental to genetic to epigenetic factors. Epigenetic regulation holds a crucial role in tumorigenesis and its progression. Epigenetics refers to alterations in the genome that happen without any changes to the DNA sequence itself; they may be triggered by multiple factors ranging from environmental to dietary factors. It includes methylation of DNA and histone modifications. Histone modifications, including histone methylation, histone acetylation, and histone ubiquitination, play a crucial role in the pathogenesis and progression of prostate cancer. These epigenetic modifications via transcriptional regulation affect key cellular processes and are thus implicated in prostate cancer and other cancers. These epigenetic markers could be used as both diagnostic and prognostic markers and also could be used as novel therapeutic targets against prostate cancer and other malignancies. Here in this review article, we have summarized different histone modifications and their mechanistic and therapeutic implications in prostate cancer.